Analisis Kesalahan Penggunaan Bahasa Ejaan pada Pamflet pada Media Luar Ruang - Sahri Nova Yoga (Medan Resource Center, 2026)
Correct spelling is essential for ensuring clarity, readability, and the effectiveness of written communication in public spaces. This study aims to identify and analyze spelling errors found in pamphlets displayed in outdoor media, with particular attention to the use of punctuation marks and italic formatting in accordance with Indonesian spelling conventions. The research employed a qualitative approach using a descriptive method by examining linguistic elements in selected pamphlets. The findings reveal two predominant types of errors. First, many pamphlets use excessive punctuation marks at the end of sentences, whereas a single punctuation mark is sufficient to convey emphasis. Second, several pamphlets incorrectly apply italic typeface to ordinary sentences, despite the fact that italics are conventionally reserved for writing the titles of books, magazines, newspapers, or other specific linguistic forms in accordance with Indonesian orthographic standards. The study concludes that greater adherence to standardized spelling rules is necessary to improve the linguistic quality and communicative effectiveness of outdoor public media while promoting proper language use in society.